2004
DOI: 10.1097/00002030-200410210-00007
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic and clinical responses to highly active antiretroviral therapy over 50 years of age. Results from the French Hospital Database on HIV

Abstract: Patients over 50 years of age have an immunologic response to HAART. However, their CD4 cell reconstitution is significantly slower than in younger patients, despite a better virologic response. This impaired immunologic response may explain their higher risk of clinical progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
124
4
8

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(157 citation statements)
references
References 30 publications
21
124
4
8
Order By: Relevance
“…22,23 Among the HL cases in our cohort that occurred during the first 3 months of cART, mean within-patient changes in CD4 count were similar to changes in the cohort overall. 21 We observed individual cases who had very rapid increases in CD4 count leading up to HL diagnosis, but our data are too sparse to assert that these events contributed to HL. Changes within individuals have not been evaluated to corroborate the shift reported from a low CD4/CD8 ratio to total lymphocytopenia during the 1-2 years before HL diagnosis.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…22,23 Among the HL cases in our cohort that occurred during the first 3 months of cART, mean within-patient changes in CD4 count were similar to changes in the cohort overall. 21 We observed individual cases who had very rapid increases in CD4 count leading up to HL diagnosis, but our data are too sparse to assert that these events contributed to HL. Changes within individuals have not been evaluated to corroborate the shift reported from a low CD4/CD8 ratio to total lymphocytopenia during the 1-2 years before HL diagnosis.…”
Section: Discussionmentioning
confidence: 74%
“…21 Specifically, of the 9 HL cases with available data, CD4 count increased by a mean of 30 cells/mm 3 over a mean of 50 days on cART before HL diagnosis. There was, however, heterogeneity: CD4 count increased steeply (9.8 cells/ mm 3 /d over 14-20 days) before diagnosis in 2 HL cases; less steeply in 2 other HL cases (1.6 cells/mm 3 /d over 57-71 days); and …”
Section: Resultsmentioning
confidence: 94%
“…[71][72][73][74][75][76][77] Interestingly, this finding is not explained by differences in virological response, as older HIV-infected patients tend to have a superior virological outcome when compared with younger patients. [78][79][80][81][82][83] Some suggests that these finding may be linked with higher adherence in older patients, 78,[84][85] but other authors reported a higher risk of inadequate adherence in HIV patients who have other comorbidities and take other medications besides HAART. [86][87] While virological response seems not to be influenced by age, at least biologically, older patients have lower CD4C T-cell gain compared with younger persons, [88][89][90][91][92][93][94][95] even when adjusted for antiretroviral therapy regimens.…”
Section: Clinical Outcomementioning
confidence: 99%
“…Based on recent sentinel surveillance data, the national adult prevalence rate is estimated at 6.6% (1). The introduction of highly active antiretroviral therapy (HAART) in 1997 has markedly improved the length of survival and the morbidity of HIV-infected patients through the improvement of the immunodeficiency caused by HIV infection (2)(3)(4)(5)(6)(7)(8)(9)(10). In recent years, the management of human immunodeficiency virus positive individuals has been based on HAART comprising a combination of nucleoside analogue reverse transcriptase inhibitors and at least one protease inhibitor and/or one non-nucleoside analogue reverse transcriptase inhibitor (11).…”
mentioning
confidence: 99%